A comprehensive reanalysis of Spitzer's 4.5 μm phase curves, and the phase variations of the ultra-hot Jupiters MASCARA-1b and KELT-16b. Issue 3 (15th April 2021) - Bell, Taylor J; Dang, Lisa; Cowan, Nicolas B; Bean, Jacob; Désert, Jean-Michel; Fortney, Jonathan J; Keating, Dylan; Kempton, Eliza; Kreidberg, Laura; Line, Michael R; Mansfield, Megan; Parmentier, Vivien; et al.
ABSTRACT: We have developed an open-source pipeline for the analysis of Spitzer /IRAC channel 1 and 2 time-series photometry, incorporating some of the most popular decorrelation methods. We applied this pipeline to new phase curve observations of ultra-hot Jupiters MASCARA-1b and KELT-16b, and we performed the first comprehensive reanalysis of 15 phase curves. We find that MASCARA-1b and KELT-16b have phase offsets of 6^+11_-11 ^° W and 38^+16_-15 ^° W, dayside temperatures of 2952^+100_-97 and 3070^+160_-150 K, and nightside temperatures of 1300^+340_-340 and 1900^+430_-440 K, respectively. We confirm a strong correlation between dayside and irradiation temperatures with a shallower dependence for nightside temperature. We also find evidence that the normalized phase curve amplitude (peak-to-trough divided by eclipse depth) is correlated with stellar effective temperature. In addition, while our different models often retrieve similar parameters, significant differences occasionally arise between them, as well as between our preferred model and the literature values. Nevertheless, our preferred models are consistent with published phase offsets to within −8 ± 21 degrees (−1.6 ± 3.2 sigma), and normalized phase curve amplitudes are on average reproduced to within −0.01 ± 0.24 (−0.1 ± 1.6 sigma). Finally, we find that BLISS performs best in most cases, but not all; we therefore recommend future analyses consider numerous detector models to ensure an optimal fit and to assess model dependencies.